PRAKTIK PERSAINGAN BISNIS DALAM USAHA LAUNDRY : Studi Kasus di Kota Sigli - Hamdiyah Hamdiyah (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2019)
This study aims to determine business competition in the Laundry business in the City of Sigli, what factors cause business competition in the Laundry business in the City of Sigli. Overview of Islamic law on business competition in the Laundry business in the City of Sigli. This type of research is field research using descriptive analysis method. The data collection using observation techniques, interviews, and documentation. The results of the study show that business competition in the laundry business occurs in marketing strategies and laundry wage prices, marketing strategies promoting sales of services by distributing brochures, and using a laundry shuttle system, as well as providing low prices to regular customers. The price of Wangi laudry wages Rp 5,000 per Kilogram. Factors that cause business competition in the laundry laundry business are economic factors, willingness factors or the desire to obtain large profits, by a lack of knowledge of religious knowledge. The review of Islamic law on Laundry business competition, is not in accordance with Islamic law due to differences in the prices of fellow laundry, the price is set below the standard price. This causes other people to suffer losses, tyranny, and cause elements of irrelevance on both sides. Therefore it is expected that laundry businesses can compete fairly with fellow laudry businesses, and not set prices below the standard price.